2014
DOI: 10.1038/srep05097
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetrically interacting spreading dynamics on complex layered networks

Abstract: The spread of disease through a physical-contact network and the spread of information about the disease on a communication network are two intimately related dynamical processes. We investigate the asymmetrical interplay between the two types of spreading dynamics, each occurring on its own layer, by focusing on the two fundamental quantities underlying any spreading process: epidemic threshold and the final infection ratio. We find that an epidemic outbreak on the contact layer can induce an outbreak on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
179
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 224 publications
(189 citation statements)
references
References 63 publications
3
179
0
3
Order By: Relevance
“…This research provides vital insight in terms of the efficiency of vaccination under different circumstances, yet empirical networks usually have particular topology properties that require special care. This includes taking into account community structure [170,188,[329][330][331][332], changes in the network structure over time [52,218,[333][334][335][336][337], as well as multilayer properties that are typical for a large plethora of real-world networks [203,231,240,241,[338][339][340][341][342][343][344][345][346][347]. In what follows, we will review vaccination programs that take into account the particular aspects of these properties on various types of networks.…”
Section: Vaccination On Other Types Of Networkmentioning
confidence: 99%
“…This research provides vital insight in terms of the efficiency of vaccination under different circumstances, yet empirical networks usually have particular topology properties that require special care. This includes taking into account community structure [170,188,[329][330][331][332], changes in the network structure over time [52,218,[333][334][335][336][337], as well as multilayer properties that are typical for a large plethora of real-world networks [203,231,240,241,[338][339][340][341][342][343][344][345][346][347]. In what follows, we will review vaccination programs that take into account the particular aspects of these properties on various types of networks.…”
Section: Vaccination On Other Types Of Networkmentioning
confidence: 99%
“…The study of the reconnection mechanism from the point of network nodes is mainly concerned with the study of the heterogeneity of link rewiring. Song et al [13] presented rewiring mechanism based on spatial distance by giving a distance measure to divide the nodes, and assumed the short distance rewiring probability is 1-p, and the long distance rewiring probability is p. The experimental results show that disconnecting the long distance link and establishing short distance link can effectively suppress the infectious disease. Rattana et al [14] established a link rewiring radius according to the geographical network establishment, and gave out the link rewiring mechanism based on the spatial distance.…”
Section: Introductionmentioning
confidence: 94%
“…In particular, the spread of diseases results in elevated crisis awareness and thus facilitates the diffusion of the awareness about the disease [6], but the diffusion of the awareness promotes more people to take preventive measures and consequently suppresses the epidemic spreading [4]. To understanding how awareness diffusion can mitigate epidemic outbreaks, and more broadly, the asymmetric interacting spreading dynamics led to a new direction of research in complex network science [7][8][9][10][11][12][13][14]. A pioneering step in this direction was taken by Clara [7] who studied the epidemic spreading in the multiplex networks by establishing two layers network, in which one represents epidemic spreading and another represents the diffusion of the information awareness.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretically existing studies found that promoting the spreading dynamics could induce distinct critical phenomena with different outbreak thresholds and critical exponents [8]. Practically speaking, promoting the spreading dynamics could shed some lights on the propagation of information [9][10][11], marketing management [12,13], disease spreading [14][15][16][17][18], etc. Many strategies for promoting spreading dynamics have been proposed, such as choosing influential seeds [19,20] and designing effective contact strategies [21,22].…”
Section: Introductionmentioning
confidence: 99%